Transformational Leadership on Performance with Locus of Control as Moderating - Zacharias, Tehubijuluw; Laurens, Samson (Action Research Literate, 2023)
This study aims to analyze the influence of transformational leadership on performance with locus of control as moderating of Bappeda employees of Maluku Province. This study uses a descriptive-quantitative approach with a causal correlation type. The research was conducted at Bappeda Maluku Province. The population used in this study were all employees at the Bappeda of Maluku Province, consisting of 86 people. Determining the number of samples is based on the sample table developed by Issac and Michael, where if the population is 86 people, then at a 5% confidence level, the number of samples is determined as many as 79 people. Data were analyzed using path analysis.The results of the study concluded that (1) transformational leadership has a positive and significant effect on the performance of Bappeda Maluku Province employees, (2) transformational leadership has a positive and significant effect on the locus of control of Bappeda employees in Maluku Province, (3) locus of control has a positive and significant effect on performance Maluku Province Bappeda employees, (4) transformational leadership has a positive and significant effect on performance through locus of control Maluku Province Bappeda employees.